Development of a Digital Flipbook on the Role of K.H. Abu Mansur in the Spread of Islam - Erika Ayu Pratiwi; Najib Jauhari (Criksetra: Jurnal Pendidikan Sejarah, 2025)
History as a subject tends to be less favored by many students. During the learning process, students often display low levels of attention and motivation. This issue is largely due to the lack of contextual and interactive teaching materials. A similar condition was observed in grade X-6 of SMAN 1 Boyolangu Tulungagung, where students showed low enthusiasm toward history learning. In response, the researcher developed digital teaching materials focusing on the role of K.H. Abu Mansur in the spread of Islam, specifically for grade X-6 of SMAN 1 Boyolangu Tulungagung. The materials were developed using the R&D method by Sugiyono. The aim was to produce teaching materials that meet the criteria of validity, feasibility, and effectiveness, while also enhancing students' learning motivation. The results showed that the flipbook teaching material was highly valid, with a material validity score of 89.9% and a content validity score of 91.1%. Small and large group trials yielded practicality percentages of 79% and 89.4%, respectively, indicating a high level of practicality. Student motivation increased significantly from 46.6% (low) to 80% (high). Theoretically, this study supports the development of digital technology-based history learning strategies. Practically, the developed materials offer an alternative to boost student motivation and engagement in history learning.